PTU-001 Propanolol at modest dose does not impair survival in patients with cirrhosis and refractory ascites. (28th May 2012) - Robins, A E; Bowden, A; Watson, W; Smith, F; Gelson, W T; Griffiths, W J
Abstract : Introduction: A recent study suggesting β-blockers should be contra-indicated in cirrhotic patients with refractory ascites has gained significant attention. 1 We sought to examine this hypothesis in a cohort of patients undergoing elective paracentesis in a tertiary liver unit. Methods: We retrospectively studied 114 consecutive patients undergoing regular paracentesis between July 2007 and December 2010 at Addenbrooke's Hospital. 36 patients were maintained on propanolol for variceal prophylaxis, whereas 78 were not β-blocked. Mortality and morbidity were compared between the two groups. The χ 2, Mann–Whitney and Kaplan–Meier methods were employed for statistical analysis. Results: There was no statistically significant difference between the two groups in terms of age, sex, aetiology of liver disease (predominantly alcohol), Child-Pugh score and UKELD. Hepatocellular carcinoma was present in 16% of patients in the propanolol group and 13% of the non β-blocked group (p=0.62). Varices were predictably present more in the propanolol group compared with the non β-blocked group (97% vs 59%, p<0.001). The mean total daily dose of propanolol used was 48.9 mg. The incidence of spontaneous bacterial peritonitis was similar between the propanolol group and non β-blocked group (43% vs 50%, p=0.51). The incidence of overt encephalopathy was also no different (43% vs 44%, p=0.93). Variceal bleeding occurred more frequently in the propanolol group compared with the non β-blocked group (69% vs 41%, p<0.01). Median survival was 18 months in the propranolol group vs 11 months in the non-propanolol group, with no significant difference between Kaplan–Meier survival curves (p=0.93, log rank test) (Abstract PTU-001 figure 1 ). Conclusion: This study demonstrates that propanolol used in a total daily dose of between 40 and 80 mg is safe in patients with cirrhosis and refractory ascites. Deleterious effects at higher doses cannot be excluded. Notwithstanding this limitation and the retrospective nature of the analysis, these data reassure regarding the use of β-blockers in this patient group and that such drugs should not be immediately contraindicated. Competing interests: None declared. Reference: 1. Serste T, Melot C, Francoz C, et al . Deleterious effects of beta-blockers on survival in patients with cirrhosis and refractory ascites. Hepatology 2010;52 :1017–22.